Controversies in the detection of neural autoantibodies - Philippa Pettingill; Thashi Chang; Sarosh Irani; Patrick Waters (Advances in Clinical Neuroscience & Rehabilitation, 2016)
The last 15 years has seen the discovery of treatable antibody-mediated CNS diseases. The accurate detection of specific antibodies helps support patient diagnosis, treatment and predict prognosis. Here we discuss some of the limitations of different antibody detection technologies, caveats in study designs that impacts on the interpretation of assays for routine clinical use and highlight a lack of data on serum versus CSF testing in this new field of neuroimmunology.